Putting Civil Society in Its Place : Governance, Metagovernance and Subjectivity - Jessop, Bob (Book collections on Project MUSE., 2020)
Through theories of metagovernance and case studies of mobilisations against economic and social problems, Bob Jessop explores the idea of civil society as a mode of governance. Reviewing concepts of self-emancipation and self-responsibilisation, he challenges conventional thinking and identifies lessons for future social innovation.